Varieties of egalitarianism: gender ideologies in the late socialism of the German Democratic Republic - Kleinschrot, Leonie; Berth, Felix; Bujard, Martin (The history of the family, 2023)
The socialist German Democratic Republic (GDR) in the east part of former divided Germany, which existed between 1949 and 1990, saw the emancipation of women as a national objective. In this paper we examine the gender ideologies of young people in the GDR in relation to state socialist ideas of gender equality. First, we outline the GDR’s socialist state policy in favour of maternal full-time employment, even with young children, between the 1950s and the 1980s. We then present the results of our analysis of gender ideologies using survey data collected by the GDR’s Central Institute of Youth Research in 1984. By applying latent class analysis, we identify two patterns of egalitarianism in the analytic sample, which we term ‘all-inclusive-egalitarians’ and ‘not-in-my-backyard-egalitarians’ (‘nimby-egalitarians’). The former supported gender equality in both the public and familial spheres. The nimby-egalitarians, by contrast, had ambivalent attitudes, as they supported gender equality in the public sphere and at the same time held more traditional attitudes towards the private sphere. Our study demonstrates that after almost 40 years of propagating gender equality, state socialism in the GDR had some success in shaping societal gender ideologies. However, we reveal ambivalences which researchers have previously often overseen, especially in contrast to the Western part of Germany. The top-down shaped GDR patterns of egalitarianism also bear similarities to the stalled gender revolution in contemporary Western democratic societies. Beyond the results, the paper proves the richness and principle usability of hitherto rarely used data sets preserved from the GDR.
Gesehen am 29.11.2023